Abandonment and management in Spanish dehesa systems: Effects on soil features and plant species richness and composition (Forest Ecology and Management, 2009)
Quercus pyrenaica dehesas have been traditionally used as communal extensive grazing systems in the Leo´n province (NW Spain). In this region, recent abandonment of rural areas and the subsequent gradual decrease in livestock load have led to the invasion of shrubs in the understory, increasing the risk of fires. Indeed, even if there is no need of creating new pasturelands for livestock breeding, the remaining landowners keep on burning to clear these montane patches. Alternatively, the regional administration encourages shrub cutting as a better way of managing these areas and preserving the pasturelands. Our aim was to determine the effects of the dehesa abandonment and shrub cutting on plant species richness (annual herbs, perennial herbs and woody plants) and species composition, as well as on topsoil properties. For that, we compared three types of dehesas with differentmanagement regimes: (1) grazed dehesas (used at the present), (2) abandoned dehesas (more than 20 years without grazing) and (3) dehesas where shrub cutting was applied after abandonment (i.e. cleared dehesas). We selected three replicates or stands per dehesa type. The highest organic matter content (O.M.), total nitrogen (N) and available phosphorus (P) were found in cleared dehesas, while the lowest values corresponded to the grazed ones. Abandoned dehesas were characterized by the highest values for available calcium (Ca2+). No significant differences were detected regarding the vegetation richness values (S alpha, gamma or beta), although higher mean values of S alpha and gamma were found in grazed dehesas, and lower values in the cleared ones. Concerning the vegetation life forms, grazed dehesas held significantly greater species richness and cover of annual herbs, while abandoned dehesas had significantly higher woody species cover. Both grazed and abandoned dehesas harboured plant species (38 and 13 species, respectively),which were exclusively found in one dehesa type. Contrary to that, cleared dehesas scarcely had ‘‘exclusive’’ species. To conclude, our results indicated that shrub cutting alone (not followed by livestock grazing) may cause loss of plant species richness, suggesting that it is not the most appropriate management method to restore vegetation, except for reducing the risk of fire.

Plant and carabid beetle species diversity in relation to forest type and structural heterogeneity (European Journal of Forest Research, 2008)
The aim of this study was to evaluate the inﬂuence of forest structure (mainly resulting from human uses) and forest type (the identity of the dominant tree species) on biodiversity. We determined the diversity of two taxonomical groups: the understory vegetation and the edaphic carabid beetle fauna. We selected eight types of forest ecosystems (ﬁve replicates or stands per forest type): pine (Pinus sylvestris) plantations of three age classes (10, 40 and 80 years since reforestation), an old-growth relict natural pine forest, and four types of oak (Quercus pyrenaica) stands: mature forests with livestock grazing and ﬁrewood extraction, mature forests where uses have been abandoned, ‘‘dehesa’’ ecosystems and shrubby oak ecosystems. The results obtained by a global PCA analysis indicated that both tree size and dominant species inﬂuenced the ordination of the 40 forest stands. In general, carabids were more sensitive to changes in forest heterogeneity and responded more clearly to the analysed structural variables than the understory vegetation, although the species richness of both groups was signiﬁ- cantly correlated and higher in case of oak forests. Pine forest ecosystems were characterised by the lowest species richness for both taxonomical groups, the lowest plant diversity and by the lowest coefﬁcients of variation and, consequently, low structural heterogeneity. As a result, it was very difﬁcult to discriminate the effects of the spatial heterogeneity and the dominant tree species on biodiversity

Plant and carabid beetle species diversity in relation to forest type and structural heterogeneity - Taboada, Ángela; Tárrega, Reyes; Calvo, Leonor; Marcos, Elena; Marcos, José Antonio; Salgado, José María (European Journal of Forest Research, 2008)
The aim of this study was to evaluate the inﬂuence of forest structure (mainly resulting from human uses) and forest type (the identity of the dominant tree species) on biodiversity. We determined the diversity of two taxonomical groups: the understory vegetation and the edaphic carabid beetle fauna. We selected eight types of forest ecosystems (ﬁve replicates or stands per forest type): pine (Pinus sylvestris) plantations of three age classes (10, 40 and 80 years since reforestation), an old-growth relict natural pine forest, and four types of oak (Quercus pyrenaica) stands: mature forests with livestock grazing and ﬁrewood extraction, mature forests where uses have been abandoned, ‘‘dehesa’’ ecosystems and shrubby oak ecosystems. The results obtained by a global PCA analysis indicated that both tree size and dominant species inﬂuenced the ordination of the 40 forest stands. In general, carabids were more sensitive to changes in forest heterogeneity and responded more clearly to the analysed structural variables than the understory vegetation, although the species richness of both groups was signiﬁ- cantly correlated and higher in case of oak forests. Pine forest ecosystems were characterised by the lowest species richness for both taxonomical groups, the lowest plant diversity and by the lowest coefﬁcients of variation and, consequently, low structural heterogeneity. As a result, it was very difﬁcult to discriminate the effects of the spatial heterogeneity and the dominant tree species on biodiversity
Keywords: Biodiversity; carabid beetles; heterogeneity; oak forests; pine plantations; understory vegetation

Forest structure and understory diversity in Quercus pyrenaica communities with different human uses and disturbances - Tárrega, Reyes; Calvo, Leonor; Marcos, Elena; Taboada, Ángela (Forest Ecology and Management, 2006)
The aim is to compare the diversity of the understory in Quercus pyrenaica communities according to the type of human intervention (grazing, obtaining wood or ﬁrewood, forest ﬁres). This interaction results in a modiﬁcation of the characteristics of the arboreal layer and shrub cover. Four types of oak communities were selected, each with ﬁve replicates: communities with a high density of shrubby oak (oak shrublands), open woodlands (‘‘dehesas’’), mature oak woods with abundant woody biomass in the understory and mature oak woods with little woody biomass in the understory. In each study site, we quantiﬁed the size of the trees (height, trunk perimeter and crown diameter) and their density, woody cover in the understory and species richness as well as diversity using the Shannon index, on both a small scale (per m 2 ) and for the total of each community. A clear difference was observed between the dehesas and the oak shrublands, the two community types with higher human intervention (the dehesas, with sustainable use for grazing and the oak shrublands, the most degraded due to repeated ﬁres), in the principal components analysis carried out with these variables. The other two community types, considered more mature forests, presented an intermediate location on the principal components analysis. However, there was no clear relationship between the different community types and the diversity values. No differences were observed in total species richness, except that the number of annuals being signiﬁcantly higher in the dehesas. Nor was it possible to detect any differences using the Shannon index, except for the oak shrublands which, although with a great variability among them, had a lower mean diversity than the other community types. The distance between trees was positively correlated to diversity, measured using the Shannon index, and to annual species richness and negatively correlated to woody cover in the understory. The variability in the distance between trees (associated with clumped distributions) was positively correlated to spatial heterogeneity, measured as Sb. The size of the trees had very little correlation to species diversity. As a whole, the results obtained show the difﬁculty involved in making generalised conclusions on the effects of disturbances on plant diversity
Keywords: annuals; Density; diversity; human intervention; land-use history; Oak trees; perennial herbs; Quercus pyrenaica; size; woody species

Forest structure and understory diversity in Quercus pyrenaica communities with different human uses and disturbances (Forest Ecology and Management, 2006)
The aim is to compare the diversity of the understory in Quercus pyrenaica communities according to the type of human intervention (grazing, obtaining wood or ﬁrewood, forest ﬁres). This interaction results in a modiﬁcation of the characteristics of the arboreal layer and shrub cover. Four types of oak communities were selected, each with ﬁve replicates: communities with a high density of shrubby oak (oak shrublands), open woodlands (‘‘dehesas’’), mature oak woods with abundant woody biomass in the understory and mature oak woods with little woody biomass in the understory. In each study site, we quantiﬁed the size of the trees (height, trunk perimeter and crown diameter) and their density, woody cover in the understory and species richness as well as diversity using the Shannon index, on both a small scale (per m 2 ) and for the total of each community. A clear difference was observed between the dehesas and the oak shrublands, the two community types with higher human intervention (the dehesas, with sustainable use for grazing and the oak shrublands, the most degraded due to repeated ﬁres), in the principal components analysis carried out with these variables. The other two community types, considered more mature forests, presented an intermediate location on the principal components analysis. However, there was no clear relationship between the different community types and the diversity values. No differences were observed in total species richness, except that the number of annuals being signiﬁcantly higher in the dehesas. Nor was it possible to detect any differences using the Shannon index, except for the oak shrublands which, although with a great variability among them, had a lower mean diversity than the other community types. The distance between trees was positively correlated to diversity, measured using the Shannon index, and to annual species richness and negatively correlated to woody cover in the understory. The variability in the distance between trees (associated with clumped distributions) was positively correlated to spatial heterogeneity, measured as Sb. The size of the trees had very little correlation to species diversity. As a whole, the results obtained show the difﬁculty involved in making generalised conclusions on the effects of disturbances on plant diversity